Analysis of high-voltage DC fuse's ageing characteristics under the overload pulse current carrying mode and the caused short-circuit failure in series-resonant converter power source. (May 2020) - Zhang, Yu; Su, Jiancang; Zheng, Lei; Li, Rui; Yu, Binxiong; Shang, Wei
Highlights: DC1600V32A fuse ageing Mechanism and high-frequency overload pulse current carrying effect. Four ageing stages of fuse conductor are revealed under high-frequency overload pulse current carrying. The lifetime evaluation way of the high-frequency overload pulse fuse is put forward. Several ways for improving the fuse conductor ageing are put forward. Abstract: As a key component in short-circuit protection, high-voltage fast DC fuse is broadly employed in high-power charge sources. In this paper, the overload pulse current carrying and ageing effect of high-voltage fast DC fuse which is used in series-resonant converter power source for short-circuit protection, is studied and analyzed. Main focus is on the mechanism of the DC1600V/32A fuse ageing and the following cut-out effect under the condition of high-frequency overload pulse current carrying. The effects on the full-bridge series-resonant converter charge source after the fuse ageing and breaking are also analyzed. The ageing under pulse currents is mainly caused by the repeated attacks of the heating-up and cooling on the fuse conductor. Four encountered stages of the fuse conductor under the high-frequency overload pulse current carrying are put forward in order, such as the linear ageing stage, the non-linear ageing stage, the fusing and arcing stage, and the arc extinguishing stage. In the linear ageing stage which plays as the available fuse life time, the fuse conductor carries the pulse currents normally and the temperature rise and fuse resistance Rf both increase linearly. When the increment ratio of Rf reaches 10%, the fuse starts to work in the non-linear ageing stage in which Rf increases nonlinearly and the series-resonant period of the charge circuit is prolonged. As the alternately opening switches in the H-bridge of the series-resonant converter are mismatched, the H-bridge is in short-circuit error, or the phenomena of the 'hard switching' and the failure for series-resonance occur. The circuit simulation and experimental results both demonstrate the H-bridge short-circuit error in series-resonant converter charge source is induced by the ageing of the fuse conductor under the overload pulse current carrying condition. In view of that, several ways for improving the fuse conductor ageing are put forward.